Surface-functionalized ionic liquid crystal-supported ionic liquid phase materials: Ionic liquid crystals in mesopores - Kohler, Florian; Morain, Bruno; Weiß, Alexander; Laurin, Mathias; Libuda, Jörg; Wagner, Valentin; Melcher, Berthold Ulrich; Wang, Xinjiao; Meyer, Karsten; Wasserscheid, Peter (ChemPhysChem, 2011)
The influence of confinement on the ionic liquid crystal (ILC) [C C Im][OTf] is studied using differential scanning calorimetry (DSC), polarized optical microscopy (POM), and diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS). The ILC studied is supported on Si-based powders and glasses with pore sizes ranging from 11 to 50 nm. The temperature of the solid-to-liquid-crystalline phase transition seems mostly unaffected by the confinement, whereas the temperature of the liquid-crystalline-to-liquid phase transition is depressed for smaller pore sizes. A contact layer with a thickness in the order of 2 nm is identified. The contact layer exhibits a phase transition at a temperature 30 K lower than the solid-to-liquid-crystalline phase transition observed for the neat ILC. For applications within the "supported ionic liquid phase (SILP)" concept, the experiments show that in pores of diameter 50 nm a pore filling of α>0.4 is sufficient to reproduce the phase transitions of the neat ILC. © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.